Forage seed production - International Livestock Centre for Africa (International Livestock Centre for Africa, 1994)
This manual has been prepared for use by trainees and trainers of forage seed production. It is intended as a practical guide to cover some of the basic principles of production of quality forage seeds. The manual is divided into five chapters. The first chapter outlines field multiplication practices including production systems, site selection, matching the forage to the site, the type of forage plant, crop establishment, crop management, and seed harvesting. The second chapter is on post-harvest seed conditioning. This involves threshing, winnowing, drying, cleaning, packaging and storage. The third chapter discusses seed quality control concepts with particular reference to assurance, testing, sampling, moisture content determination, purity analysis, germination testing, viability testing and seed certification and legislation. The fourth chapter deals with seed marketing while the fifth chapter highlights the economics of forage seed production.